Variability in division of popliteal artery - Ziemiański, Anrzej; Malinowski, Andrzej; Jurczykowski , Tadeusz (Anthropological Review, 1974)
The results of arteriographic research work in 108 lower male extermities have bcen presented which concerned with the division of the popliteal artery. The place where the frontal tibial artery separated from the politeral artery was in 4.63% above the fissure of the knee-joint in 7.41% on a level with the fisstire or up to 3 cm below it. In most of the examined subjects this division was found from 2 cm to 6 cm below this fissure. Separations at a low level below 6 cm from the fissure occurred in 11.11%. When te frontal tibial artery separates from the politeal artery at a high level the angles are almost right the lower the levels of division the more obtuse are the angles. The length of the posterior fibula-tibial stem in subjects under examination ranged from lcm to 12cm. A short stem up to 2 cm in length occurred in 7.41% while a long stem over 6 cm in 10.18%.A normal division of popliteal artery existed in 93.5% of examined subjects, in 1.86% the fibular artery was absent and in 4.63% a frontal fibula-tibial stem was found. The absence of a posterior fibula-tibial stem occurred in 6.48%. The fibular artery was a rather frequent prolongation of the popliteal artery and the posterior tibial artery separated at the point from which the posterior fibula-libial stem has divided.